FORMATION OF THE PEDAGOGICAL PROCESS IN TEACHING RUSSIAN MEDICAL TERMINOLOGY - Rozanna Abdullaeva (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2023)
The formation of the pedagogical process is one of the urgent tasks of modern medical education. Pedagogical conditions in the article are understood as the components of the educational process, ensuring the achievement of its goals and objectives. Factors and circumstances resulting from the targeted selection, design and application of content elements, methods, and organizational forms of learning to achieve certain didactic goals.